EXPERIMENTAL DESIGNS AS A TRANSVERSAL COMPETENCE FOR AGRICULTURAL TRAINING: CURRICULAR INTEGRATION, PRACTICAL APPLICATIONS AND METHODOLOGICAL CHALLENGES - García Hevia, Segress; Cárdenas García, Sheila; Cárdenas García, Rachel; Torres Tene, Rubén (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2025)
Contemporary agricultural education demands professionals capable of leading innovation through the application of rigorous methodological tools. Among these, experimental design emerges as a key transversal competence for developing applied research in agricultural systems. This study presents a critical review of academic literature and technical reports (2010–2024), aiming to identify the state of the art, key experimental design typologies, their pedagogical applications, and teaching challenges. The findings reveal a gap between theoretical instruction and practical application, along with limited integration of digital technologies and active methodologies. Guidelines are proposed for curriculum modernization, faculty training in applied statistics, and strengthening research networks in agricultural education.
Keywords: Experimental designs; agricultural systems; teaching and learning